O Retrato de Edmond Belamy e a interface entre arte e inteligencia artificial: por uma nova definição de autoria e direitos de propriedade intelectual = The Portrait of Edmond Belamy and the interface between art and artificial intelligence: for a new definition of autorship and intellectual property rights - Mangiolardo, Marla Meneses do Amaral Leite (2020)
- DOI: 10.5102/rdi.v17i3.7191